The Acceptance of Utilizing Rice Husk Ash (RHA) in Non-Autoclaved Aerated Concrete Among Construction Stakeholders - Mohd Noh, Hamidun; Azahar, Nor Shahidah; Idris, Nur’ain; Kasim, Narimah; Zainal, Rozlin; Shareh Musa, Sharifah Meryam (Research in Management of Technology and Business, 2021)
Recently, the use of aerated concrete is become popular among construction stakeholder due to the lightness, strength and the durability factor. However, the increase in demand of concrete. causes the price of raw material to increase as well. Moreover, the production of cement contributes significantly to air pollution which is the emission of carbon dioxide. On the other hand, rice husk ash is one of the waste material which have a big population and potential to be used in construction due to the high volume of silica content in this research, rice husk ash is used in the concrete as a partial cement replacement in order to reduce the dependency. The research objectives in this study are to identify the factors that influences the types of material used in producing a concrete cube in concrete manufacturing, to investigate the potential acceptance of rice husk ash as a sub-material in concrete among the manufacturer and to initiate in improving the products. This study was conducted by interviewing the people related in the construction industry or the manufacturer on the acceptance of the rice husk ash as a replacement in non-autoclaved aerated concrete. The result of this study is to prove that RHA could be used in the concrete mixture as a replacement to cement with a good structural strength and environmental friendly and create an awareness between the manufacturer regarding the matters. This study is also expected to educate the society in reducing and managing the rice husk waste and explore in the potential ways of using the waste as an alternative sub-material.